Green body, antique porcelain tile and preparation method thereof
By controlling the composition and process of the blank, calcium and sodium feldspar is generated to reduce the shrinkage rate of the blank. The two firing process and glaze layer design are used to solve the size error and pattern alignment of the antique ceramic tile, and the quality of the product is improved. consistency.
Patent Information
- Application Number
- CN202411326895.8
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-09-23
- Publication Date
- 2025-01-07
AI Technical Summary
In the existing antique ceramic tile preparation methods, the high shrinkage rate of the blank leads to large product size errors and difficult to guarantee the pattern alignment accuracy.
By controlling the amount of CaO and Na2O in the blank, calcium and soda feldspar is generated to fill the gaps and reduce the shrinkage rate. The two firing processes are used for vegetarian firing and glaze firing, combining the design of the surface glaze layer and the protective glaze layer to ensure that the blank is Uniformity and pattern alignment accuracy of body and product.
It significantly reduces the shrinkage rate of antique porcelain tiles, improves the product's dimensional consistency and pattern alignment accuracy, and avoids foaming and prickly heat defects caused by excessive calcium oxide.
Smart Images

Figure CN119263797A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of ceramic product firing, and more specifically, to a green body, an antique porcelain tile and a preparation method thereof. Background Art
[0002] Antique brick products were first introduced from abroad, and then they were digested, absorbed and innovated by Chinese people to produce new building ceramic products. From a technical point of view, antique bricks evolved from glazed bricks, and are essentially glazed porcelain bricks. The use function and cultural connotation of antique bricks have been expanded to a larger field of architectural decoration. As a product with elegant cultural elements, the application scope of antique bricks has been expanded very wide.
[0003] Most antique tiles are made of porcelain. At present, the production of antique tiles usually involves glazing and inkjetting the blanks after they are formed and dried, and then firing them once to produce the product. In practice, it is found that the antique porcelain tiles produced by the traditional one-time firing process have a high shrinkage rate, which leads to large size errors in the same batch of products, and the accuracy of pattern alignment is difficult to guarantee.
[0004] In view of this, it is necessary to improve the existing preparation method or formula of antique tiles to overcome the problems existing in the prior art. Summary of the invention
[0005] The present invention aims to overcome at least one defect of the above-mentioned prior art and provide a green body, an antique porcelain tile and a preparation method thereof, which are used to solve the problem of high shrinkage rate.
[0006] The first aspect of the present invention provides a green body, wherein the green body is prepared from a green body comprising the following chemical components in parts by weight: 66-68 parts SiO 2 , 17-19 parts Al 2 O 3 、0.1-1.8 parts Fe 2 O 3 , 0.1-0.3 parts TiO 2 , 2-3 portions of K 2 O, 1.8-3.0 parts Na 2 O, 1-2 parts MgO, 2.0-3.4 parts CaO.
[0007] In the present invention, CaO and Na 2The weight fraction of O is specifically limited, so that it reacts with other chemical components during the firing process to form calcium-sodium feldspar. Since calcium-sodium feldspar has a silicon-oxygen tetrahedral structure, on the one hand, it can fill the gaps well during the solid phase reaction to reduce local shrinkage, so that the overall shrinkage uniformity of the blank after firing is good. On the other hand, it can maintain good stability based on its specific silicon-oxygen tetrahedral structure during the cooling reaction. Therefore, the product can better maintain the original size and significantly reduce the shrinkage rate. The blank of the present invention is used as the embryo layer of antique porcelain tiles. After applying the surface glaze and protective glaze, the glaze firing process is carried out. Based on the filling and supporting role of calcium-sodium feldspar, the shrinkage rate of the final product of antique porcelain tiles can be avoided to be too large, thereby improving the pattern alignment accuracy of antique porcelain tiles and improving the quality.
[0008] Furthermore, the CaO and the Na 2 The weight ratio of O is 5:6-9:5.
[0009] The proportion of the invention can ensure that labradorite is generated by firing, while avoiding the undesirable phenomenon of bubbles appearing during the firing process of the green body due to excessive calcium oxide.
[0010] Furthermore, the blank used to prepare the blank includes the following raw materials in parts by weight: 3-7 parts of wollastonite, 12-15 parts of potassium and sodium feldspar powder, 10-14 parts of sodium feldspar powder 4, 8-12 parts of sodium feldspar powder 5-1, 12-16 parts of sand paste, 2-4 parts of mixed clay, 1-3 parts of waste brick particles, 9-13 parts of raw clay, 12-16 parts of bentonite, 2-5 parts of magnesia clay, 2-5 parts of environmentally friendly clay, 0.1-2 parts of water-coal slurry slag, and 8-10 parts of environmentally friendly mud.
[0011] By combining the above-mentioned amounts of wollastonite with other raw materials, calcium sodium feldspar can be generated during the firing process of the blank, and the undesirable phenomenon of foaming caused by excessive CaO can be avoided.
[0012] The second aspect of the present invention is to provide an antique porcelain tile, which comprises a body layer, a surface glaze layer, and a protective glaze layer from bottom to top, wherein the body layer adopts the aforementioned body.
[0013] Furthermore, the surface glaze layer includes a first surface glaze layer and a second surface glaze layer from bottom to top, the first surface glaze layer is applied on the surface of the body layer, and the second surface glaze layer is applied on the surface of the first surface glaze layer.
[0014] The third aspect of the present invention is to provide a method for preparing the antique porcelain tile, comprising the following steps:
[0015] The blank is subjected to a forming process to obtain the blank, and the blank is subjected to biscuit firing to obtain a biscuit;
[0016] The first surface glaze layer and the second surface glaze layer are sequentially applied on the surface of the blank, and then the protective glaze layer is applied on the second surface glaze layer, and then the antique porcelain tile is obtained through glaze firing treatment.
[0017] In the present invention, after the blank is bisque-fired to obtain a blank, the water absorption rate and shrinkage rate of the blank are both reduced compared with the original blank, and then the first surface glaze layer, the second surface glaze layer and the protective glaze layer are applied in sequence on the surface of the blank, and the antique porcelain tile is obtained after glaze firing. Since the blank has a smaller shrinkage rate, during the glaze firing process, the overall shrinkage rate of the antique porcelain tile is significantly reduced compared with the conventional one-time firing process, thereby reducing the pattern alignment deviation of the surface glaze layer, so that the sizes of the antique porcelain tile products in the same batch have good consistency, and the quality of the antique porcelain tiles is significantly improved.
[0018] Furthermore, before forming the first glaze layer on the surface of the blank, the process further includes the following steps: correcting the size deviation of the blank.
[0019] Preferably, the size deviation of the blank is corrected by chamfering correction.
[0020] The present invention adopts a double-firing process, and it is possible to perform a size deviation correction on the biscuit after biscuit firing to improve the consistency of size before the second firing, and also improve the overall uniformity of the same biscuit. In this way, the shrinkage rate of the final product after glaze firing can be reduced, and the pattern alignment deviation can be reduced.
[0021] Furthermore, before forming the protective glaze layer on the second surface glaze layer, the method further includes the following steps: performing inkjet printing on the surface of the second surface glaze layer.
[0022] Furthermore, the biscuit sintering ambient temperature is 1050-1150° C., and the sintering period is 30-40 minutes.
[0023] Furthermore, the water absorption rate of the green blank is 8-12%, and the shrinkage rate is 3-5%.
[0024] Furthermore, the ambient temperature of the glaze firing is 1100-1200°C, and the firing cycle is 30-40 minutes.
[0025] Furthermore, the water absorption rate of the antique porcelain tile is 0.01-0.05%, and the shrinkage rate during the glaze firing process is 4-6%.
[0026] Furthermore, the first glaze used to prepare the first glaze layer includes the following chemical components in parts by weight: 59-61 parts SiO 2 、24-26.5 parts Al 2 O 3 , 0.1-0.3 parts Fe 2 O 3 , 0.1-0.2 parts TiO2 , 0.1-0.3 parts CaO, 1-1.5 parts MgO, 1-1.5 parts K 2 O, 3-5 parts Na 2 O, 4-7 parts ZrO 2 .
[0027] Furthermore, the specific gravity of the first glaze is 1.82-1.88 g / cm 3 , the glaze amount is 83-87g.
[0028] Furthermore, the second glaze used to prepare the second glaze layer includes the following chemical components in parts by weight: 43-47 parts SiO 2 , 11-14 parts Al 2 O 3 , 0.1-0.3 parts Fe 2 O 3 , 0.1-0.2 parts TiO 2 , 4-6 parts CaO, 4-6 parts MgO, 1.5-2.5 parts K 2 O, 2-4 parts Na 2 O, 2-4 parts ZrO 2 , 9-11 parts of BaO, 5-7 parts of ZnO.
[0029] Furthermore, the specific gravity of the second glaze is 1.82-1.88 g / cm 3 , the glaze amount is 70-74g.
[0030] Furthermore, the protective glaze used to prepare the protective glaze layer includes the following chemical components in parts by weight: 47-50 parts SiO 2 , 19-21 parts of Al 2 O 3 , 0.1-0.5 parts Fe 2 O 3 , 0.1-0.2 parts TiO 2 , 11-13 parts CaO, 1-2 parts MgO, 1.5-2.5 parts K 2 O, 3-3.8 parts Na 2 O, 2-4 parts of BaO, 2-5 parts of ZnO.
[0031] Furthermore, the specific gravity of the protective glaze is 1.12-1.18 g / cm 3 , the glaze amount is 23-27g.
[0032] Compared with the prior art, the invention has the following beneficial effects: 1) by 2O specific restrictions on the amount of two chemical components, thereby promoting the formation of calcium sodium feldspar during bisque firing, based on the filling and supporting role of calcium sodium feldspar, reducing the shrinkage rate of the body after bisque firing, improving the overall shrinkage uniformity of the body, and also helping to reduce the overall shrinkage rate of antique porcelain tiles after glaze firing, so that the pattern alignment accuracy is improved; 2) by adding a specific amount of wollastonite raw material to the body formula, while ensuring the formation of calcium sodium feldspar after bisque firing of the body, it also avoids the foaming phenomenon caused by excessive CaO, thereby improving the quality of antique porcelain tiles; 3) by increasing the bisque firing of the body The process is used to produce the blank, which effectively reduces the shrinkage rate of the blank, and then it is possible to add a size correction process to the blank before applying the glaze, thereby improving the consistency of the blank size, further reducing the shrinkage rate of the product after glaze firing, and improving the pattern positioning accuracy; 4) By improving the formula of the first glaze and the second glaze, the water absorption rate of the glaze layer and the blank layer is made close, avoiding the premature closure of the blank during glaze firing, further improving the pattern positioning accuracy of the antique porcelain tile, and making the first glaze and the second glaze meet the secondary firing process requirements of low-temperature biscuit firing + high-temperature glaze firing. BRIEF DESCRIPTION OF THE DRAWINGS
[0033] Figure 1 .XRD phase diagram of the green body layer provided in Example 3. DETAILED DESCRIPTION
[0034] The first aspect of the present invention provides a green body, wherein the green body is prepared from a green body comprising the following chemical components in parts by weight: 66-68 parts SiO 2 , 17-19 parts Al 2 O 3 、0.1-1.8 parts Fe 2 O 3 , 0.1-0.3 parts TiO 2 , 2-3 portions of K 2 O, 1.8-3.0 parts Na 2 O, 1-2 parts MgO, 2.0-3.4 parts CaO.
[0035] The test found that by CaO and Na 2The weight fraction of O is specifically limited, so that it reacts with other chemical components during the firing process to form calcium-sodium feldspar. Calcium-sodium feldspar has a silicon-oxygen tetrahedral structure. On the one hand, it can fill the gaps well during the solid phase reaction to reduce local shrinkage, so that the overall shrinkage uniformity of the green body after firing is good. On the other hand, it can provide good stability based on its specific silicon-oxygen tetrahedral structure during the cooling reaction. Therefore, the product can better maintain the original size and significantly reduce the shrinkage rate. In actual use, the prepared green body is used as the embryo layer of antique porcelain tiles. After applying the surface glaze and protective glaze, the glaze firing process is carried out. Based on the filling and supporting role of calcium-sodium feldspar, the shrinkage rate of the final product of antique porcelain tiles can be avoided to be too large, thereby improving the pattern alignment accuracy of antique porcelain tiles and improving the quality.
[0036] In some embodiments, CaO and Na 2 The weight ratio of O is 5:6-9:5.
[0037] Experiments show that the molecular formula of sodium calcium feldspar is (Ca, Na)(Si, Al) 4 O 8 , when CaO and Na 2 When the weight ratio of CaO to NaO is less than 5:6, about 20% of the free sodium is removed as flux during the firing process, and the free calcium is still relatively insufficient relative to the remaining free sodium, resulting in an insufficient proportion of the final generated calcium-sodium feldspar, and the voids in the green body cannot be fully filled. Therefore, it is difficult to effectively curb the shrinkage of the green body after biscuit firing. On the other hand, when CaO and Na 2 When the weight ratio of O is greater than 9:5, the free calcium is obviously excessive relative to the free sodium during the firing process. Although the proportion of calcium-sodium feldspar generated is sufficient to fully fill the voids in the green body and thus reduce the shrinkage of the green body, the excess free calcium causes excess CaO in the final product, resulting in blistering in the green body and causing the antique porcelain tile to have prickly heat defects.
[0038] In some embodiments, the blank used to prepare the green blank includes the following raw materials in parts by weight: 3-7 parts of wollastonite, 12-15 parts of potassium and sodium feldspar powder, 10-14 parts of sodium feldspar powder 4, 8-12 parts of sodium feldspar powder 5-1, 12-16 parts of sand paste, 2-4 parts of mixed clay, 1-3 parts of waste brick particles, 9-13 parts of raw clay, 12-16 parts of bentonite, 2-5 parts of magnesia clay, 2-5 parts of environmentally friendly clay, 0.1-2 parts of water-coal slurry slag, and 8-10 parts of environmentally friendly mud.
[0039] Tests show that by combining the above-mentioned amounts of wollastonite with other raw materials, calcium sodium feldspar can be generated during the firing process of the blank, thereby filling and supporting the voids in the blank, significantly reducing the shrinkage rate, and avoiding the undesirable phenomenon of foaming caused by excessive CaO.
[0040] The second aspect of the present invention is to provide an antique porcelain tile, which comprises a body layer, a surface glaze layer and a protective glaze layer from bottom to top, wherein the body layer adopts the above-mentioned body.
[0041] Tests show that, since the above-mentioned green body has a smaller shrinkage rate during the firing process, the overall shrinkage rate of the antique porcelain tile after firing can be reduced, thereby reducing dimensional deviation and improving pattern alignment accuracy.
[0042] In specific implementation, in order to improve the quality of antique porcelain tiles, the surface glaze layer includes a first glaze layer and a second glaze layer from bottom to top. The first glaze layer is applied on the surface of the body layer, and the second glaze layer is applied on the surface of the first glaze layer. In specific application, the first glaze layer can play the effect of cosmetic soil, improve the fineness of the antique porcelain tiles, and make the texture clear.
[0043] The third aspect of the present invention is to provide a method for preparing the antique porcelain tile, comprising the following steps:
[0044] The blank is subjected to a forming process to obtain a blank body, and the blank body is subjected to biscuit firing to obtain a biscuit;
[0045] A first glaze layer and a second glaze layer are sequentially applied on the surface of the blank, and a protective glaze layer is formed on the second glaze layer. After that, the antique porcelain tile is obtained by glaze firing.
[0046] In the present invention, the water absorption rate and shrinkage rate of the biscuit obtained by biscuit firing are both reduced compared with the original biscuit body, and then the first surface glaze layer, the second surface glaze layer and the protective glaze layer are applied in sequence on the surface of the biscuit body, and the antique porcelain tile is obtained after glaze firing. The present invention effectively reduces the shrinkage rate of the final product through the two preparation methods of biscuit firing + glaze firing, and reduces the pattern alignment error of the surface glaze layer during the firing process, thereby reducing the size deviation of products in the same batch and improving the quality of the antique porcelain tile.
[0047] In some embodiments, before forming the first glaze layer on the surface of the blank, the following step is further included: correcting the size deviation of the blank. Preferably, the size deviation of the blank is corrected by chamfering correction.
[0048] In the specific production process, factors such as different firing positions and uneven molding pressures are difficult to completely overcome, resulting in the inevitable size deviations of the biscuit fired by biscuit, such as large and small heads and narrow waists. Since the present invention adopts a two-firing process, it is possible to correct the size deviation of the biscuit after biscuit firing, thereby improving the consistency of size before the second firing, and also improving the overall uniformity of the same biscuit. In this way, the shrinkage rate of the final product after glaze firing can be reduced, and the pattern alignment deviation can be reduced.
[0049] In some embodiments, in order to form a preset pattern, before forming the protective glaze layer on the second glaze layer, the following step is also included: inkjet printing is performed on the surface of the second glaze layer.
[0050] In some embodiments, the biscuit sintering temperature is 1050-1150° C., and the sintering period is 30-40 min.
[0051] In some embodiments, the water absorption rate of the green blank is 8-12%, and the shrinkage rate is 3-5%.
[0052] In some embodiments, the ambient temperature of the glaze firing is 1100-1200° C., and the firing period is 30-40 minutes.
[0053] In some embodiments, the water absorption rate of the prepared antique porcelain tile is 0.1-0.5%, and the shrinkage rate during the glaze firing process is 4-6%.
[0054] In some embodiments, the first glaze used to prepare the first glaze layer includes the following chemical components in parts by weight: 59-61 parts SiO 2 、24-26.5 parts Al 2 O 3 , 0.1-0.3 parts Fe 2 O 3 , 0.1-0.2 parts TiO 2 , 0.1-0.3 parts CaO, 1-1.5 parts MgO, 1-1.5 parts K 2 O, 3-5 parts Na 2 O, 4-7 parts ZrO 2 .
[0055] In a specific implementation, the first glaze used to prepare the first glaze layer may use the following raw materials in parts by weight: 3 parts of calcined talc, 9 parts of zirconium silicate, and 88 parts of a first glaze base material; wherein the first glaze base material includes the following chemical components in parts by weight: 61-64 parts of SiO 2 , 28-30 parts Al 2 O 3 , 0.1-0.5 parts Fe 2 O 3 , 0.1-0.2 parts TiO 2 , 0.1-0.2 parts CaO, 0.1-0.2 parts MgO, 1-1.5 parts K 2 O, 3-5 parts Na 2 O.
[0056] Tests show that when the first glaze adopts the above-mentioned chemical composition and / or raw material formula, the sintering temperature of the first glaze layer can be lowered, and the water absorption rate of the first glaze layer and the above-mentioned body layer can be made close, thereby reducing the inversion after sintering. If the sintering temperature of the glaze layer is lowered in the first sintering process, premature closure is likely to occur, resulting in continued oxidation and decomposition of carbonates, silicates, etc. in the body to produce gas, forming prickly heat defects. The present invention adopts a secondary firing process, and the body has been completely bisque-fired, and there is no continued reaction. Therefore, it is only necessary to sinter the glaze layer at a relatively low temperature.
[0057] In some embodiments, a first glaze is applied on the surface of the blank by a bell jar glazing method, and the specific gravity of the first glaze is 1.82-1.88 g / cm 3 , flow rate is 28-32s, glaze amount is 83-87g (300*600 standard iron plate).
[0058] In some embodiments, the second glaze used to prepare the second glaze layer includes the following chemical components in parts by weight: 43-47 parts SiO 2 , 11-14 parts Al 2 O 3 , 0.1-0.3 parts Fe 2 O 3 , 0.1-0.2 parts TiO 2 , 4-6 parts CaO, 4-6 parts MgO, 1.5-2.5 parts K 2 O, 2-4 parts Na 2 O, 2-4 parts ZrO 2 , 9-11 parts of BaO, 5-7 parts of ZnO.
[0059] In a specific implementation, the second glaze used to prepare the second glaze layer can use the following raw materials in parts by weight: 1 part of air knife clay, 3 parts of calcite, 4 parts of zirconium silicate, 1 part of calcined zinc oxide 99, and 100 parts of the second glaze base material; wherein the second glaze base material includes the following chemical components in parts by weight: 46-50 parts of SiO 2 , 12-14 parts Al 2 O 3 , 0.1-0.3 parts Fe 2 O 3 , 0.1-0.2 parts TiO 2 , 3-5 parts CaO, 4-6 parts MgO, 1-3 parts K 2 O, 3-5 parts Na 2 O, 0.1-0.5 parts ZrO 2 , 10-12 parts of BaO, 4-6 parts of ZnO.
[0060] Experiments show that when the second glaze uses the above chemical composition formula and / or raw material formula, the sintering temperature of the second glaze layer can be lowered, and the water absorption rate of the second glaze layer and the above green body layer can be made close, thereby reducing the inversion after sintering.
[0061] In some embodiments, the second glaze is applied on the surface of the first glaze layer by bell jar glazing, and the specific gravity of the second glaze is 1.82-1.88 g / cm 3 , flow rate is 28-32s, glaze amount is 70-74g (300*600 standard iron plate).
[0062] In some embodiments, the protective glaze used to prepare the protective glaze layer includes the following chemical components in parts by weight: 47-50 parts SiO 2 , 19-21 parts of Al 2 O 3 , 0.1-0.5 parts Fe 2 O 3 , 0.1-0.2 parts TiO 2 , 11-13 parts CaO, 1-2 parts MgO, 1.5-2.5 parts K 2 O, 3-3.8 parts Na 2 O, 2-4 parts of BaO, 2-5 parts of ZnO.
[0063] In specific implementation, a protective glaze can be applied on the surface of the second glaze layer by spraying, and the specific gravity of the protective glaze is 1.12-1.18 g / cm 3 , flow rate is 11-15s, glaze amount is 23-27g (300*600 standard iron plate).
[0064] About the raw materials involved in the present invention:
[0065] Sand paste: purchased from Foshan Shangfengyu Building Materials Co., Ltd.
[0066] The chemical composition of sand paste is shown in the following table:
[0067] chemical composition <![CDATA[SiO 2 ]]> <![CDATA[Al 2 THE 3 ]]> <![CDATA[Fe 2 THE 3 ]]> <![CDATA[TiO 2 ]]> <![CDATA[K 2 The]]> <![CDATA[Na 2 The]]> MgO CaO Weight 49-53 29-33 2.5-3.5 0.1-0.5 3-5 0.1-0.5 0.1-0.5 0.01-0.10
[0068] Raw clay: purchased from Guangzhou Jinsheng Mining Trading Co., Ltd.
[0069] The chemical composition of raw clay is shown in the following table:
[0070] chemical composition <![CDATA[SiO 2 ]]> <![CDATA[Al 2 THE 3 ]]> <![CDATA[Fe 2 THE 3 ]]> <![CDATA[TiO 2 ]]> <![CDATA[K 2 The]]> <![CDATA[Na 2 The]]> MgO CaO Weight 65-69 18-22 2-3 0.4-0.8 1-2 0.1-0.5 0.1-0.5 0.3-0.7
[0071] Magnesium clay: purchased from Pingxiang Hongyan Materials Co., Ltd.
[0072] The chemical composition of magnesium mud is shown in the following table:
[0073] chemical composition <![CDATA[SiO 2 ]]> <![CDATA[Al 2 THE 3 ]]> <![CDATA[Fe 2 THE 3 ]]> <![CDATA[TiO 2 ]]> <![CDATA[K 2 The]]> <![CDATA[Na 2 The]]> MgO CaO Weight 57-61 2.5-3.5 0.5-1.0 0.1-0.5 0.1-0.5 0.1-0.5 19-23 1-3
[0074] Mixed clay: purchased from Foshan Zhishuntong Ceramic Raw Materials Co., Ltd.
[0075] The chemical composition of the mixed mud is shown in the following table:
[0076] chemical composition <![CDATA[SiO 2 ]]> <![CDATA[Al 2 THE 3 ]]> <![CDATA[Fe 2 THE 3 ]]> <![CDATA[TiO 2 ]]> <![CDATA[K 2 The]]> <![CDATA[Na 2 The]]> MgO CaO Weight 68-72 16-20 1-3 0.2-0.7 0.1-0.5 0.3-0.7 1-3 0.3-0.7
[0077] The chemical composition of waste brick particles is shown in the following table:
[0078] chemical composition <![CDATA[SiO 2 ]]> <![CDATA[Al 2 THE 3 ]]> <![CDATA[Fe 2 THE 3 ]]> <![CDATA[TiO 2 ]]> <![CDATA[K 2 The]]> <![CDATA[Na 2 The]]> MgO CaO Weight 69-73 17-21 1-2 0.1-0.5 1.5-3.5 1-3 1-2 1-2
[0079] The chemical composition of environmentally friendly mud is shown in the following table:
[0080] chemical composition <![CDATA[SiO 2 ]]> <![CDATA[Al 2 THE 3 ]]> <![CDATA[Fe 2 THE 3 ]]> <![CDATA[TiO 2 ]]> <![CDATA[K 2 The]]> <![CDATA[Na 2 The]]> MgO CaO Weight 64-68 17-21 1-3 0.1-0.5 2-3 2-3 1-2 1-2
[0081] Sodium feldspar powder 4: purchased from Zhaoqing Zhongcheng New Materials Co., Ltd.
[0082] Sodium feldspar powder 5-1: purchased from Zhaoqing Zhongcheng New Materials Co., Ltd.
[0083] The chemical composition of environmentally friendly mud is shown in the following table:
[0084] chemical composition <![CDATA[SiO 2 ]]> <![CDATA[Al 2 THE 3 ]]> <![CDATA[Fe 2 THE 3 ]]> <![CDATA[TiO 2 ]]> <![CDATA[K 2 The]]> <![CDATA[Na 2 The]]> MgO CaO Weight 65-68 18-20 1-2 0.1-0.4 2-3 2-3 1-2 1-2
[0085] The chemical composition of coal water slurry slag is shown in the following table:
[0086]
[0087]
[0088] Among them, the numerical suffixes of raw materials such as potassium and sodium feldspar powder 6, sodium feldspar powder 4, sodium feldspar powder 5-1, sand paste 31, mixed clay 20, raw clay 20, bentonite 14, and magnesia clay 21 are mainly used to reflect the component composition of the raw materials, which is a common identification method in this field.
[0089] The following will be combined with the embodiments of the present invention to clearly and completely describe the technical solutions in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.
[0090] The experimental methods used in the following examples are conventional methods unless otherwise specified. The materials, reagents, methods and instruments used are conventional materials, reagents, methods and instruments in the art unless otherwise specified, and can be obtained through commercial channels by those skilled in the art.
[0091] Example 1
[0092] This embodiment provides a method for preparing antique porcelain tiles, and the specific steps are as follows:
[0093] S01. The raw material workshop processes the antique blanks, processes the blanks by a press molding machine, and obtains a blank;
[0094] S02. The green body obtained in step S01 is subjected to biscuit sintering treatment, the ambient temperature is set to 1095°C, the firing cycle is 36min, and a green body is obtained. After testing, the green body has a water absorption rate of 10% and a shrinkage rate of 4% during the biscuit sintering process;
[0095] S03. The product obtained in step S02 is glazed by glazing lines, that is, the blank is used as the blank layer, and the first glaze and the second glaze are applied on the blank layer in sequence, and then inkjet printing and protective glaze are applied, and then glaze firing is performed, and the ambient temperature is set to 1160°C, and the firing cycle is 36 minutes, so that the first glaze layer, the second glaze layer, and the protective glaze layer are stacked from bottom to top on the blank layer, and the antique porcelain tile is obtained. After testing, the water absorption rate of the antique porcelain tile in this embodiment is 0.03%, and the shrinkage rate during the glaze firing process is 5.5%;
[0096] S04. Grinding the edges of the antique porcelain tiles obtained in step S03 and packaging them.
[0097] The blank used in step S01 includes the following raw materials in parts by weight:
[0098] Table 1. Raw material formula of Example 1 blank
[0099]
[0100] The blank used in step S01 includes the following chemical components in parts by weight:
[0101] Table 2. Chemical composition of the blank of Example 1
[0102] chemical composition <![CDATA[SiO 2 ]]> <![CDATA[Al 2 THE 3 ]]> <![CDATA[Fe 2 THE 3 ]]> <![CDATA[TiO 2 ]]> <![CDATA[K 2 The]]> <![CDATA[Na 2 The]]> MgO CaO IL(Loss on Ignition) Number of copies 67.98 18.48 1.69 0.26 2.49 2.02 1.35 0.80 4.82
[0103] The first glaze component formula in step S03 is as follows:
[0104] Table 3. Raw material formula of the first glaze of Example 1
[0105] Components Burnt Talc Zirconium silicate First glaze base Number of copies 3 9 88
[0106] The first glaze base material includes the following chemical components in parts by weight:
[0107] Table 4. Chemical composition of the first glaze base material of Example 1
[0108] chemical composition <![CDATA[SiO 2 ]]> <![CDATA[Al 2 THE 3 ]]> <![CDATA[Fe 2 THE 3 ]]> <![CDATA[TiO 2 ]]> CaO MgO <![CDATA[K 2 The]]> <![CDATA[Na 2 The]]> IL Number of copies 62.8 29.12 0.24 0.15 0.22 0.11 1.36 4.42 1.5
[0109] The first glaze comprises the following chemical components in parts by weight:
[0110] Table 5. Chemical composition of the first glaze of Example 1
[0111] chemical composition <![CDATA[SiO 2 ]]> <![CDATA[Al 2 THE 3 ]]> <![CDATA[Fe 2 THE 3 ]]> <![CDATA[TiO 2 ]]> CaO MgO <![CDATA[K 2 The]]> <![CDATA[Na 2 The]]> <![CDATA[ZrO 2 ]]> IL Number of copies 60.09 25.81 0.22 0.15 0.22 1.05 1.22 3.90 5.81 1.40
[0112] The second glaze in step S03 includes the following raw materials in parts by weight:
[0113] Table 6. Raw material formula of the second glaze of Example 1
[0114] Components Air knife soil Calcite Zirconium silicate Calcined zinc oxide 99 Second glaze base Number of copies 1 3 4 1 100
[0115] The second glaze base material includes the following chemical components in parts by weight:
[0116] Table 7. Chemical composition of the second glaze base material of Example 1
[0117] chemical composition <![CDATA[SiO 2 ]]> <![CDATA[Al 2 THE 3 ]]> <![CDATA[Fe 2 THE 3 ]]> <![CDATA[TiO 2 ]]> CaO MgO <![CDATA[K 2 The]]> <![CDATA[Na 2 The]]> <![CDATA[ZrO 2 ]]> BaO ZnO IL Number of copies 47.72 13.51 0.19 0.09 3.82 5.06 1.99 3.6 0.01 11.2 5.09 7.5
[0118] The second glaze includes the following chemical components in parts by weight:
[0119] Table 8. Chemical composition of the second glaze of Example 1
[0120] name <![CDATA[SiO 2 ]]> <![CDATA[Al 2 THE 3 ]]> <![CDATA[Fe 2 THE 3 ]]> <![CDATA[TiO 2 ]]> CaO MgO <![CDATA[K 2 The]]> <![CDATA[Na 2 The]]> <![CDATA[ZrO 2 ]]> BaO ZnO IL Number of copies 45.4 12.8 0.2 0.1 5.0 4.7 1.8 3.3 2.4 10.2 5.6 8.2
[0121] The protective glaze in step S03 includes the following chemical components in parts by weight:
[0122] Table 9. Chemical composition of protective glaze of Example 1
[0123] chemical composition <![CDATA[SiO 2 ]]> <![CDATA[Al 2 THE 3 ]]> <![CDATA[Fe 2 THE 3 ]]> <![CDATA[TiO 2 ]]> CaO MgO <![CDATA[K 2 The]]> <![CDATA[Na 2 The]]> BaO ZnO IL Number of copies 49.24 20.17 0.46 0.13 12.59 1.65 1.69 3.25 2.93 2.89 4.57
[0124] Example 2
[0125] This embodiment provides a method for preparing antique porcelain tiles. Compared with the embodiment 1, this embodiment further includes S021 between S02 and S03: chamfering the blank to correct the size deviation such as narrow waist, large and small head;
[0126] The specific process steps of implementation 2 are as follows:
[0127] S01. The raw material workshop processes the antique blanks, processes the blanks by a press molding machine, and obtains a blank;
[0128] S02. The green body obtained in step S01 is subjected to biscuit sintering treatment, the ambient temperature is set to 1095°C, the firing cycle is 36min, and a green body is obtained. After testing, the green body has a water absorption rate of 10% and a shrinkage rate of 4% during the biscuit sintering process;
[0129] S021. Chamfering the blank obtained in step S02;
[0130] S03. The product obtained in step S021 is glazed by glazing lines, that is, the blank is used as the blank layer, and the first glaze and the second glaze are applied on the blank layer in sequence, and then inkjet printing and protective glaze are applied, and then glaze firing is performed, and the ambient temperature is set to 1160°C, and the firing cycle is 36 minutes, so that the first glaze layer, the second glaze layer, and the protective glaze layer are stacked from bottom to top on the blank layer, and the antique porcelain tile is obtained. After testing, the water absorption rate of the antique porcelain tile in this embodiment is 0.03%, and the shrinkage rate is 5.5%;
[0131] S04. Grinding the edges of the antique porcelain tiles obtained in step S03 and packaging them.
[0132] Among them, the component formula and chemical composition of the blank of this embodiment, the component formula and chemical composition of the first glaze, the component formula and chemical composition of the second glaze, and the component formula and chemical composition of the protective glaze are all consistent with those in Example 1.
[0133] According to the test, the antique porcelain tile of this embodiment has a water absorption rate of 0.03% and a shrinkage rate of 5.5% during the glaze firing process.
[0134] Example 3
[0135] This embodiment provides a method for preparing antique porcelain tiles, and the specific steps are exactly the same as those of Example 2. The only difference from Example 2 is that the raw material formula and chemical composition of the blank are different.
[0136] Specifically, the blank of this embodiment includes the following raw materials in parts by weight:
[0137] Table 10. Raw material formula of Example 3 blank
[0138]
[0139] The blank of this embodiment includes the following chemical components in parts by weight:
[0140] Table 11. Chemical composition of the blank of Example 3
[0141] chemical composition <![CDATA[SiO 2 ]]> <![CDATA[Al 2 THE 3 ]]> <![CDATA[Fe 2 THE 3 ]]> <![CDATA[TiO 2 ]]> <![CDATA[K 2 The]]> <![CDATA[Na 2 The]]> MgO CaO IL Number of copies 67.20 18.18 1.68 0.26 2.38 1.87 1.30 2.33 4.80
[0142] Except for the blank, the component formula and chemical composition of the first glaze, the second glaze and the protective glaze of this embodiment are consistent with those of Example 2.
[0143] In this embodiment, CaO and Na 2 O by weight, specifically, to control the ratio of CaO to Na 2 O weight ratio is in the range of 5:6-9:5, so that Figure 1As shown, the green body layer of the present embodiment reacts to generate labradorite during the bisque firing process. Labradorite has a silicon-oxygen tetrahedral structure. On the one hand, it can fill the voids well during the solid phase reaction to reduce local shrinkage, so that the overall shrinkage uniformity of the green body after firing is good. On the other hand, it can provide good stability during the cooling reaction based on its specific silicon-oxygen tetrahedral structure. Therefore, the product can better maintain the original size and significantly reduce the shrinkage rate.
[0144] After testing, the green body of this embodiment has a water absorption rate of 8.0% after bisque firing, and a shrinkage rate of 3.2% during the bisque firing process; the antique porcelain tile obtained in this embodiment has a water absorption rate of 0.03%, and a shrinkage rate of 4.47% during the glaze firing process.
[0145] Comparative Example 1
[0146] This comparative example provides a method for preparing antique porcelain tiles, which adopts a one-time firing method, and the specific steps are as follows:
[0147] T1. The raw material workshop processes antique blanks, processes the blanks by press molding, and obtains blanks;
[0148] T2. glaze line glazing, that is, applying the first glaze and the second glaze on the body obtained in T1, then inkjet printing, applying protective glaze, and then glaze firing, the highest firing temperature is 1160 ° C, the firing cycle is 36min, and the antique porcelain tile is obtained. After testing, the shrinkage rate of the antique porcelain tile of this comparative example is 9.84% after one firing;
[0149] T3. Grind the edges of the antique porcelain tiles obtained in step T2 and pack them.
[0150] The component formula and chemical composition of the blank and protective glaze of the comparative example are completely consistent with those of Example 1. In addition, in order to meet the requirements of the one-time firing process, the first glaze of this comparative example includes the following raw materials in parts by weight:
[0151] Table 12. Raw material formula of the first glaze of comparative example 1
[0152] Components Burnt Talc Zirconium silicate First glaze base Number of copies 1 9 90
[0153] The chemical composition of the first glaze base material in this comparative example is the same as that in Example 1.
[0154] The first glaze of this comparative example includes the following chemical components in parts by weight:
[0155] Table 13. Chemical composition of the first glaze of Comparative Example 1
[0156] chemical composition <![CDATA[SiO 2 ]]> <![CDATA[Al 2 THE 3 ]]> <![CDATA[Fe 2 THE 3 ]]> <![CDATA[TiO 2 ]]> CaO MgO <![CDATA[K 2 The]]> <![CDATA[Na 2 The]]> <![CDATA[ZrO 2 ]]> IL Number of copies 60.04 26.35 0.22 0.15 0.21 0.44 1.23 3.98 5.81 1.43
[0157] The second glaze of this comparative example includes the following raw materials in parts by weight:
[0158] Table 14. Raw material formula of the second glaze of comparative example 1
[0159] Components Air knife soil Calcite Calcined Alumina (325 mesh) Zirconium silicate Calcined zinc oxide 99 Second glaze base Number of copies 1 3 2 4 1 100
[0160] The chemical composition of the second glaze base material in this comparative example is the same as that in Example 1.
[0161] The second glaze of this comparative example includes the following chemical components in parts by weight:
[0162] Table 15. Chemical composition of the second glaze of Comparative Example 1
[0163] name <![CDATA[SiO 2 ]]> <![CDATA[Al 2 THE 3 ]]> <![CDATA[Fe 2 THE 3 ]]> <![CDATA[TiO 2 ]]> CaO MgO <![CDATA[K 2 The]]> <![CDATA[Na 2 The]]> <![CDATA[ZrO 2 ]]> BaO ZnO IL Number of copies 44.6 14.3 0.2 0.1 4.9 4.6 1.8 3.3 2.3 10.1 5.5 8.1
[0164] Comparative Example 2
[0165] This comparative example provides a method for preparing antique porcelain tiles. The specific steps are exactly the same as those of Example 3. The only difference between this comparative example and Example 3 is the component formula and chemical composition of the blank.
[0166] Specifically, the blank of this comparative example includes the following raw materials in parts by weight:
[0167] Table 16. Raw material formula of comparative example 2 blank
[0168]
[0169] The blank of this comparative example includes the following chemical components in parts by weight:
[0170] Table 17. Chemical composition of the blank of Comparative Example 2
[0171] chemical composition <![CDATA[SiO 2 ]]> <![CDATA[Al 2 THE 3 ]]> <![CDATA[Fe 2 THE 3 ]]> <![CDATA[TiO 2 ]]> <![CDATA[K 2 The]]> <![CDATA[Na 2 The]]> MgO CaO IL Number of copies 66.1 17.7 1.7 0.3 2.3 1.8 1.4 3.5 5.3
[0172] From the above chemical composition analysis, it can be seen that only the weight of CaO exceeds the upper limit of 2.0-3.4 parts specified in the present invention. 2 The weight ratio of O is 3.5:1.8, which exceeds the upper limit of 9:5 set in the present invention. Tests have found that the free calcium in the blank of this comparative example is significantly excessive relative to the free sodium during the bisque firing process, resulting in the combination of the two to form a certain amount of calcium-sodium feldspar. The excess free calcium causes bubbling in the surface glaze layer, causing the antique porcelain tiles produced by the secondary firing process to have prickly heat defects.
[0173] Comparative Example 3
[0174] This comparative example provides a method for preparing antique porcelain tiles. The specific steps are exactly the same as those of Example 3. The only difference between this comparative example and Example 3 is the component formula and chemical composition of the blank.
[0175] Specifically, the blank of this embodiment includes the following raw materials in parts by weight:
[0176] Table 18. Raw material formula of comparative example 3 blank
[0177]
[0178] The blank of this comparative example includes the following chemical components in parts by weight:
[0179] Table 19. Chemical composition of the blank of Comparative Example 3
[0180] chemical composition <![CDATA[SiO 2 ]]> <![CDATA[Al 2 THE 3 ]]> <![CDATA[Fe 2 THE 3 ]]> <![CDATA[TiO 2 ]]> <![CDATA[K 2 The]]> <![CDATA[Na 2 The]]> MgO CaO IL Number of copies 67.3 18.42 1.72 0.27 2.41 1.93 1.35 1.47 4.99
[0181] From the above chemical composition analysis, it can be seen that only the weight percentage of CaO is lower than the lower limit of 2.0-3.4 parts specified in the present invention. 2 The weight proportion of O is 1.47:1.93, which is less than the lower limit of 5:6 specified in the present invention. It is found that the amount of free calcium in the blank of this comparative example is relatively insufficient relative to free sodium during the biscuit firing process, resulting in a decrease in the proportion of calcium-sodium feldspar generated, which is insufficient to fill the voids in the blank. At this time, the area where the voids are not filled with calcium-sodium feldspar will still produce a large shrinkage rate during the firing process. Therefore, the overall shrinkage uniformity of the blank is insufficient. After testing, the blank of this comparative example obtained by biscuit firing has a water absorption rate of 14% and a shrinkage rate of 6%; the antique porcelain tile obtained by firing this comparative example has a water absorption rate of 0.02%, and a shrinkage rate of 6.5% during the glaze firing process. It can be seen that, relative to the embodiment, the shrinkage rate of the blank of this comparative example in the biscuit firing and glaze firing processes is significantly increased, which is not conducive to the accurate alignment of the surface pattern of the product.
[0182] Test Case
[0183] 1. Physical and chemical index detection of embodiments and comparative examples
[0184] Table 20. Summary of physical and chemical indicators of Examples 1-3 and Comparative Examples 1-3
[0185]
[0186] II. Example 1-3, Comparative Example 1 Product size and deviation test
[0187] For the antique porcelain tile samples prepared in Examples 1-3 and Comparative Example 1, 7 points at the same position were taken to measure the width dimensions. The test results are shown in the following table:
[0188] Table 21. Statistics of dimensions and deviations of products from different batches
[0189]
[0190]
[0191] According to the statistical results of Table 21, when the single firing process of Comparative Example 1 is adopted, the size error of products in the same batch is 4-6.5mm, and the maximum error of products in different batches reaches 7.5mm; when the secondary firing process of Examples 2 and 3 is adopted, the size error of products in the same batch can be shortened to 3.5-4.5mm, and the corrected size deviation reaches more than 2mm, which has certain advantages.
[0192] In particular, Example 3 adjusts the blank formulation, adds wollastonite, and adjusts the CaO and Na 2 The dosage ratio of O is adjusted so that calcium sodium feldspar is generated in the green body during the firing process, and the residual amount of CaO is reasonably controlled. Therefore, based on the filling and supporting effect of calcium sodium feldspar on the voids, the overall shrinkage uniformity of the green body is improved, as shown in Table 20. This makes the dimensional deviation of the product of Implementation 3 at each inspection point smaller, which helps to improve the accuracy of the product surface pattern alignment and improve the quality of the final product.
[0193] In specific implementation, according to statistics of different batches of products, when the 1200*600mm specification herringbone wood grain tile products adopt the one-time firing process as in comparative example 1, the product shrinkage is generally 9-10%, and the alignment error of the pattern is 4-5mm, which is difficult to control to ≤2mm. Referring to Table 20, when the secondary firing production as in Example 1 is adopted, after the first biscuit firing, the blank will have a shrinkage rate of 3-5%. On this basis, the process as in Examples 2 and 3 is adopted, that is, by adding a blank chamfering correction process, correcting the size deviations such as narrow waist and large and small heads, and then applying glaze printing for glaze firing, the shrinkage rate of the herringbone wood grain antique porcelain tile during the glaze firing process is about 4-6%, which is compared with the 9.5-10% shrinkage rate of the one-time firing process, which can greatly improve the accuracy of the pattern alignment. In addition, the present invention can significantly improve the strength of the green body by adding a biscuit firing process to the green body. Tests show that after the biscuit firing process of the present invention, the strength of the green body is increased from 1-2Mpa when it is a green body to 20Mpa when it is a green body. This can also meet the needs of multiple process superpositions, such as screen printing, roller printing, spraying dry particles, etc., thereby promoting the diversification of antique porcelain tile products and achieving high added value.
[0194] In particular, according to the test data of Example 3 and Comparative Examples 1 and 2, when the process of Example 3 is adopted, the raw material formula of the blank is improved, wollastonite is added, and other raw materials are appropriately adjusted, so as to control the CaO and Na in the blank. 2The weight proportion of O is 5:6-9:5, so that the ratio of the amount of free calcium and free sodium substances in the blank during the bisque firing process is appropriate. On the one hand, a sufficient amount of calcium-sodium feldspar can be generated, and on the other hand, excessive calcium oxide residue can be avoided. As a result, the water absorption and shrinkage of the blank after bisque firing are further reduced, and based on the filling and supporting effect of calcium-sodium feldspar on the voids, the overall shrinkage uniformity of the blank can be improved, thereby improving the size consistency of products in the same batch. After the blank is subsequently glazed and protected with glaze and glaze fired, the shrinkage rate of the final antique porcelain tile is significantly reduced, and the positioning accuracy of the pattern is further improved. At the same time, the defects of velvet and skin glaze products in the final product can be avoided, so as to obtain high-quality, high value-added antique porcelain tiles.
[0195] Obviously, the above embodiments of the present invention are merely examples for clearly illustrating the technical solution of the present invention, and are not intended to limit the specific implementation methods of the present invention. Any modifications, equivalent substitutions and improvements made within the spirit and principles of the claims of the present invention shall be included in the protection scope of the claims of the present invention.
Claims
1. A green body, characterized in that: The blank used to prepare the blank includes the following chemical components in parts by weight: 66-68 parts of SiO2, 17-19 parts of Al2O3, 0.1-1.8 parts of Fe2O3, 0.1-0.3 parts of TiO2, 2-3 parts of K2O, 1.8-3.0 parts of Na2O, 1-2 parts of MgO, and 2.0-3.4 parts of CaO.
2. The blank according to claim 1, characterized in that The weight ratio of the CaO to the Na2O is 5:6-9:
5.
3. The blank according to claim 1, characterized in that The blank used to prepare the blank includes the following raw materials in parts by weight: 3-7 parts of wollastonite, 12-15 parts of potassium and sodium feldspar powder, 10-14 parts of sodium feldspar powder 4, 8-12 parts of sodium feldspar powder 5-1, 12-16 parts of sand paste, 2-4 parts of mixed clay, 1-3 parts of waste brick particles, 9-13 parts of raw clay, 12-16 parts of bentonite, 2-5 parts of magnesia clay, 2-5 parts of environmentally friendly clay, 0.1-2 parts of water-coal slurry slag, and 8-10 parts of environmentally friendly mud.
4. An antique porcelain tile, characterized in that: From bottom to top, it includes a body layer, a surface glaze layer, and a protective glaze layer, wherein the body layer adopts the body described in any one of claims 1-3.
5. The antique porcelain tile according to claim 4, characterized in that: The surface glaze layer includes a first surface glaze layer and a second surface glaze layer from bottom to top. The first surface glaze layer is applied on the surface of the body layer, and the second surface glaze layer is applied on the surface of the first surface glaze layer.
6. A method for preparing an antique porcelain tile as claimed in claim 5, characterized in that: The following steps are involved: The blank is subjected to a forming process to obtain the blank, and the blank is subjected to biscuit firing to obtain a biscuit; The first surface glaze layer and the second surface glaze layer are sequentially applied on the surface of the blank, and then the protective glaze layer is applied on the second surface glaze layer, and then the antique porcelain tile is obtained through glaze firing treatment.
7. The preparation method according to claim 6, characterized in that: Before applying the first glaze layer on the surface of the blank, the method further includes the following steps: correcting the size deviation of the blank; and / or, Before applying the protective glaze layer on the second glaze layer, the method further comprises the following steps: inkjet printing on the surface of the second glaze layer; and / or, The biscuit sintering temperature is 1050-1150°C and the sintering period is 30-40 minutes; and / or, The water absorption rate of the green blank is 8-12%, and the shrinkage rate is 3-5%; and / or, The glaze firing ambient temperature is 1100-1200°C, and the firing cycle is 30-40 minutes; and / or, The water absorption rate of the antique porcelain tile is 0.01-0.05%, and the shrinkage rate during the glaze firing process is 4-6%.
8. The preparation method according to claim 6 or 7, characterized in that: The first glaze used to prepare the first glaze layer comprises the following chemical components in parts by weight: 59-61 parts of SiO2, 24-26.5 parts of Al2O3, 0.1-0.3 parts of Fe2O3, 0.1-0.2 parts of TiO2, 0.1-0.3 parts of CaO, 1-1.5 parts of MgO, 1-1.5 parts of K2O, 3-5 parts of Na2O, 4-7 parts of ZrO2; and / or, The specific gravity of the first glaze is 1.82-1.88 g / cm 3 , the glaze amount is 83-87g.
9. The preparation method according to claim 6 or 7, characterized in that: The second glaze used to prepare the second glaze layer comprises the following chemical components in parts by weight: 43-47 parts of SiO2, 11-14 parts of Al2O3, 0.1-0.3 parts of Fe2O3, 0.1-0.2 parts of TiO2, 4-6 parts of CaO, 4-6 parts of MgO, 1.5-2.5 parts of K2O, 2-4 parts of Na2O, 2-4 parts of ZrO2, 9-11 parts of BaO, 5-7 parts of ZnO; and / or, The specific gravity of the second glaze is 1.82-1.88 g / cm 3 , the glaze amount is 70-74g.
10. The preparation method according to claim 6 or 7, characterized in that: The protective glaze used to prepare the protective glaze layer includes the following chemical components in parts by weight: 47-50 parts of SiO2, 19-21 parts of Al2O3, 0.1-0.5 parts of Fe2O3, 0.1-0.2 parts of TiO2, 11-13 parts of CaO, 1-2 parts of MgO, 1.5-2.5 parts of K2O, 3-3.8 parts of Na2O, 2-4 parts of BaO, 2-5 parts of ZnO; and / or, The specific gravity of the protective glaze is 1.12-1.18 g / cm 3 , the glaze amount is 23-27g.
Citation Information
Patent Citations
Archaized brick with low sintering temperature, low radioactivity and ultrawhite whole body, green body and preparation method of green body
CN108793950A
Ceramic tile with sunken glaze effect and preparation method thereof
CN114105477A
Combination and method for obtaining bactericidal ceramic enamels for ceramic products
EP2759524A1
Method for applying rock rock irradiating far infrared ray to humman body
KR1020090131580A